(untitled) (Conferencea, 2025)
Studying the morphofunctional state of pulmonary vascular endothelium in the alloxan diabetes model as a key aspect in evaluating the impact of diabetes on the pulmonary circulatory system The study analyzed the morphometric changes in small and medium-diameter pulmonary blood vessels. It was found that alloxan diabetes leads to thickening of pulmonary capillary walls, narrowing of vessel diameters, and endothelial damage. These pathological processes are primarily associated with endothelial dysfunction, cellular degeneration, and the toxic effects of glucose. The research results revealed that diabetes causes interstitial edema, an increase in collagen deposits, and microcirculatory disruptions in pulmonary blood vessels. These morphometric changes result in hypoxia and disturbances in pulmonary circulation as complications of diabetes. The findings of this study contribute to a better understanding of pathological processes in the pulmonary vascular endothelium in diabetes and aim to develop treatment strategies in this field.